The Role of Digital Leadership in Business Performance through Digital Culture and Process Innovation in the Era of Digital Transformation - M. Faiz Afif (Proceeding of The International Conference on Business and Economics, 2026)
Digital transformation requires organizations to adapt by leveraging technology and reshaping their ways of working . In this context , digital leadership plays a crucial role in enhancing business performance . This study aims to examine the role of digital leadership on business performance through digital culture and process innovation in the era of digital transformation . This research employs a quantitative approach using a survey method involving respondents from organizations that are undergoing or have implemented digital transformation initiatives . Data were analyzed using path analysis or Structural Equation Modeling (SEM) to test both direct and indirect relationships among variables . The results indicate that digital leadership has been positive and significant effect on business performance . Furthermore , digital culture and process innovation is proven to act as mediator variables that strengthen the influence of digital leadership on business performance . These findings highlights that leaders who are able to foster digital adoption , encourage collaboration , and continuously innovate business processes can create sustainable competitive advantages for organizations . This study contributes theoretically to the development of digital leadership literature and provides practical implications for organizational leaders in designing effective digital transformation strategies aimed at improving business performance .